2023
DOI: 10.3390/land12061142
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Regenerative Agriculture Using Remote Sensing and Machine Learning

Abstract: The emergence of cloud computing, big data analytics, and machine learning has catalysed the use of remote sensing technologies to enable more timely management of sustainability indicators, given the uncertainty of future climate conditions. Here, we examine the potential of “regenerative agriculture”, as an adaptive grazing management strategy to minimise bare ground exposure while improving pasture productivity. High-intensity sheep grazing treatments were conducted in small fields (less than 1 ha) for shor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Recent studies highlight the extensive use of machine learning in RA [28,29]. To explore its potential in bioeconomic modeling, a comprehensive literature review was conducted.…”
Section: Advanced Analytical Methods Used In Broadacre Agriculturementioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies highlight the extensive use of machine learning in RA [28,29]. To explore its potential in bioeconomic modeling, a comprehensive literature review was conducted.…”
Section: Advanced Analytical Methods Used In Broadacre Agriculturementioning
confidence: 99%
“…Geographic information systems (GIS) and remote sensing (RS) aid in crop monitoring, land use planning, yield estimation, soil mapping, fertility management, vegetation and biomass assessment [153]. For example, Ogungbuyi et al [28] used machine learning and satellite imagery for remote small-scale pasture management in Australia, focusing on RA to enhance pasture productivity and reduce bare ground exposure. Their study involved biomass sampling of various pasture types (i.e., wallaby grass, kangaroo grass, Phalaris, and cocksfoot) and employed machine learning with Sentinel-2 imagery to estimate biomass.…”
Section: Advanced Analytical Methods Used In Broadacre Agriculturementioning
confidence: 99%
See 2 more Smart Citations
“…There are reports that satellite imagery has been used to model forage biomass for Phalaris aquatica and Dactylis glomerata. In that study, they used satellite remote sensing and machine learning techniques to quantify the total standing dry matter (TSDM), standing green biomass, and standing dry biomass of these two species [44]. This research demonstrated the use of remote sensing technology, specifically satellite imagery, to model forage biomass.…”
Section: Using Uavs To Estimate Forage Yield For Grasses Of Semiarid ...mentioning
confidence: 96%